Designing an Artificial Neural Network model for the prediction of kidney problems symptom through patient's metal behavior for pre- clinical medical diagnostic - Tijjani Adam, Shuwa; Uda, Hashim, Prof. Dr.; U. S., Sani (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/